10th anniversary of iPS cells: the challenges that lie ahead - Aoi, Takashi (Journal of biochemistry (Tokyo), 2016)
In 2006, induced pluripotent stem (iPS) cells were generated by Yamanaka and Takahashi for the first time from a mouse fibroblast culture by introducing four factors. In the 10 years since then, this breakthrough discovery has been making waves in the fields of biology and medical science. For example, various technologies for generating iPS cells have been developed, and we have cultivated a better understanding of the mechanisms involved in reprogramming. In addition, many researchers have explored the applications of iPS cells, such as drug discovery, the study of disease mechanisms and regenerative medicine, and the development of advanced technologies for the differentiation and qualification of the cells. Furthermore, the concept of iPS cell generation has inspired a number of studies that do not use iPS cells. We herein review and discuss the past, present and future of iPS cells and their related issues.